(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This text is a tribute to the strangeness and complexity that inhabits us. In a poetic key it weaves and crumbles at the same time, to invite us to try a fragment of the personal history that is the core of the incarnated methodology proposed by the author. Have we ever stopped to ask ourselves what it means to be human? How many times do we generate sensitivity with the fragile? The fly makes itself when it appears. It is the fly that makes us uncomfortable for all that it is, but is it not a mirror of our own being?